Targeting TF-AKT/ERK-EGFR Pathway Suppresses the Growth of Hepatocellular Carcinoma - Huang, Shan-Zhou; Wei, Meng-Ning; Huang, Jia-Rong; Zhang, Zi-Jian; Zhang, Wen-Ji; Jiang, Qi-Wei; Yang, Yang; Wang, Huan-Yu; Jin, Hui-Lin; Wang, Kun; Xing, Zi-Hao; Yuan, Meng-Ling; et al. (Frontiers in Oncology, 2019)
Tissue factor (TF) is a transmembrane glycoprotein to initiate blood coagulation and frequently overexpressed in a variety of tumors. Our previous study has showed that the expression of TF is upregulated and correlated with prognosis in hepatocellular carcinoma (HCC). However, the role and molecular mechanism of TF in the growth of HCC are still unclear. In vitro and in vivo functional experiments were performed to determine the effect of TF on the growth of HCC cells. A panel of biochemical assays was used to elucidate the underlying mechanisms. TF could promote the growth of HCC in vitro and in vivo by activating both ERK and AKT signaling pathways. TF induced EGFR upregualtion, and inhibition of EGFR suppressed TF-mediated HCC growth. In addition, TF protein expression was correlated with EGFR in HCC tissues. TF promotes HCC growth by upregulation of EGFR, and TF as well as EGFR may be potential therapeutic targets of HCC.